Evaluation of postmortem pathological changes in the lung in SARS-CoV-2 RT-PCR positive cases - Daş, Taner; Buğra, Aytül; Arslan, Murat Nihat; Ziyade, Nihan; Buyuk, Yalcin (Journal of Surgery and Medicine, 2021)
Background/Aim: The most common cause of death in COVID-19 is acute respiratory distress syndrome. Diffuse alveolar damage is the histological characteristic and counterpart of acute respiratory distress syndrome. Histopathological findings, accompanied by immunohistochemical findings, can provide valuable information in the pathogenesis of Covid-19. We aimed to investigate the histopathological findings by supporting our results with immunohistochemical staining in SARS-CoV-2 positive autopsies. Methods: A total of 101 autopsy cases with positive postmortem SARS-CoV-2 rt-PCR tests between May 2020-May 2021 were investigated in this retrospective cohort study. Cases with negative postmortem swab samples on rt-PCR and those with severe autolysis were excluded from the study. Pathological changes in the lung were examined with hematoxylin and eosin-stained preparations. Immunohistochemical assay with pancytokeratin, TTF-1, IL-6, CD68, CD3, CD8, and antibodies against the SARS-CoV-2 nucleocapsid protein were also performed for further evaluation. Results: Diffuse alveolar damage findings were present in 58 (61.7%) out of 94 cases in our study. Seventeen (18.1%) showed findings compatible with the exudative phase, 37 (39.3%) were in the proliferative phase, and 4 (4.3%) were in the fibrotic phase of diffuse alveolar damage. Pulmonary perivascular lymphocytic infiltrates contained more CD3 (+) T lymphocytes than CD8 (+) T lymphocytes, immunohistochemically. Conclusion: The finding of more CD3 positive T lymphocytes than the CD8 positive T lymphocytes in the perivascular lymphocytic infiltrate correlates with the hypothesis of the direct destruction of CD8 (+) T lymphocytes or through impairment of cellular immunity by SARS-CoV-2 induced mediators. Detection of immunohistochemical staining with IL-6 in COVID-19 supports the cytokine storm mentioned in the previous studies and the role of IL-6 in cytokine storm in SARS-CoV-2 infection. The limited number of immunohistochemical studies on SARS-CoV-2 increases the importance of our study, which evaluates IL-6, CD3, and CD8 expressions at the tissue level. Autopsy research is important and contributes to the development of protective, diagnostic, and therapeutic modalities.